Espectroscopia de infravermelho próximo na determinação da composição, perdas por cocção e força de cisalhamento de carne bovina congelada a -20 e a -40°C - BEZERRA, Robert Taylor Rocha (2009)
This study was conducted to evaluate the application of near infrared spectroscopy (NIRS) in the prediction of levels of protein, moisture, fat besides cooking losses and shear force in non-ground frozen meat under slow method -20° C and rapid -40° C. The study was conducted in two stages, the first to identify the effect of freezing on the spectra and the second for the development of equations of calibration and validation of the quantitative method for the constituents and quality factors cited. For the two stages 16 muscles Longissimus dorsi purchased at a large cold-storage building in the state of Goiás under Federal Inspection were used. The method developed to identify the effect of freezing on the spectra obtained by NIRS was able to identify 100% of the samples for the processing -20° and -40° C, with coefficients of determination (R2) greater than 0.94. After identifying the differences between the spectra according to the treatments in the first stage, the calibration was developed to create equations for moisture, protein, fat, cooking losses and shear force for each treatment. In the stage of calibration the regression analysis was developed, , taking as independent variables the results of physical-chemical analysis, and as dependent variables, the results of reflectance in the near infrared region from 1100 to 2400nm. The method showed itself effective for determining differences between spectra of Longissimus dorsi muscles subjected to freezing in temperatures of -20° and -40° C. The influence of the method of freezing on moisture and cooking losses was significant (P<0.05) on the test. The determination coefficients (R2) obtained from the relation between the analysis values by reference methods and by NIRS, for the protein, moisture and fat contents at -20° and -40°C were superior to 0,90. For shear force and cooking losses the values of R2 were superior to 0,70.